The effect of occupational exposure to noise on ischaemic heart disease, stroke and hypertension: A systematic review and meta-analysis from the WHO/ILO Joint Estimates of the Work-Related Burden of Disease and Injury. (September 2021) - Teixeira, Liliane R.; Pega, Frank; Dzhambov, Angel M.; Bortkiewicz, Alicja; da Silva, Denise T. Correa; de Andrade, Carlos A.F.; Gadzicka, Elzbieta; Hadkhale, Kishor; Iavicoli, Sergio; Martínez-Silveira, Martha S.; Pawlaczyk-Łuszczyńska, Małgorzata; Rondinone, Bruna M.; et al.
Highlights: WHO and ILO are developing joint estimates of work-related burden of disease and injury. We systematically reviewed effect of occupational exposure to noise on CVD. We found 17 eligible studies with 534, 688 participants in 11 countries/3 WHO regions. We are very uncertain about the effect of occupational exposure to noise on CVD. Abstract: Background: The World Health Organization (WHO) and the International Labour Organization (ILO) are developing joint estimates of the work-related burden of disease and injury (WHO/ILO Joint Estimates), with contributions from a large number of individual experts. Evidence from mechanistic data suggests that occupational exposure to noise may cause cardiovascular disease (CVD). In this paper, we present a systematic review and meta-analysis of parameters for estimating the number of deaths and disability-adjusted life years from CVD that are attributable to occupational exposure to noise, for the development of the WHO/ILO Joint Estimates. Objectives: We aimed to systematically review and meta-analyse estimates of the effect of any (high) occupational exposure to noise (≥85 dBA), compared with no (low) occupational exposure to noise (<85 dBA), on the prevalence, incidence and mortality of ischaemic heart disease (IHD), stroke, and hypertension. Data sources: A protocol was developed and published, applying the Navigation Guide as an organizing systematic review framework where feasible. We searched electronic academic databases for potentially relevant records from published and unpublished studies up to 1 April 2019, including International Trials Register, Ovid MEDLINE, PubMed, Embase, Lilacs, Scopus, Web of Science, and CISDOC. The MEDLINE and Pubmed searches were updated on 31 January 2020. We also searched grey literature databases, Internet search engines and organizational websites; hand-searched reference lists of previous systematic reviews and included study records; and consulted additional experts. Study eligibility and criteria: We included working-age (≥15 years) workers in the formal and informal economy in any WHO and/or ILO Member State but excluded children (<15 years) and unpaid domestic workers. We included randomized controlled trials, cohort studies, case-control studies and other non-randomized intervention studies with an estimate of the effect of any occupational exposure to noise on CVD prevalence, incidence or mortality, compared with the theoretical minimum risk exposure level (<85 dBA). Study appraisal and synthesis methods: At least two review authors independently screened titles and abstracts against the eligibility criteria at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from qualifying studies. We prioritized evidence from cohort studies and combined relative risk estimates using random-effect meta-analysis. To assess the robustness of findings, we conducted sensitivity analyses (leave-one-out meta-analysis and used as alternative fixed effects and inverse-variance heterogeneity estimators). At least two review authors assessed the risk of bias, quality of evidence and strength of evidence, using Navigation Guide tools and approaches adapted to this project. Results: Seventeen studies (11 cohort studies, six case-control studies) met the inclusion criteria, comprising a total of 534, 688 participants (39, 947 or 7.47% females) in 11 countries in three WHO regions (the Americas, Europe, and the Western Pacific). The exposure was generally assessed with dosimetry, sound level meter and/or official or company records. The outcome was most commonly assessed using health records. We are very uncertain (low quality of evidence) about the effect of occupational exposure to noise (≥85 dBA), compared with no occupational exposure to noise (<85 dBA), on: having IHD (0 studies); acquiring IHD (relative risk (RR) 1.29, 95% confidence interval (95% CI) 1.15 to 1.43, two studies, 11, 758 participants, I 2 0%); dying from IHD (RR 1.03, 95% CI 0.93–1.14, four studies, 198, 926 participants, I 2 26%); having stroke (0 studies); acquiring stroke (RR 1.11, 95% CI 0.82–1.65, two studies, 170, 000 participants, I 2 0%); dying from stroke (RR 1.02, 95% CI 0.93–1.12, three studies, 195, 539 participants, I 2 0%); having hypertension (0 studies); acquiring hypertension (RR 1.07, 95% CI 0.90–1.28, three studies, four estimates, 147, 820 participants, I 2 52%); and dying from hypertension (0 studies). Data for subgroup analyses were missing. Sensitivity analyses supported the main analyses. Conclusions: For acquiring IHD, we judged the existing body of evidence from human data to provide "limited evidence of harmfulness"; a positive relationship is observed between exposure and outcome where chance, bias, and confounding cannot be ruled out with reasonable confidence. For all other included outcomes, the bodies of evidence were judged as "inadequate evidence of harmfulness". Producing estimates for the burden of CVD attributable to occupational exposure to noise appears to not be evidence-based at this time. Protocol identifier: 10.1016/j.envint.2018.09.040 . PROSPERO registration number: CRD42018092272.